Report
1941-11 038-0024-004 6 many organisations which have co-operated and contributed, who have made this work of mercy possible, and of the unstinting labour of the regular staff, both in the "Homes" and in the London Office — who worked all hours and under great difficulties in order that these children should forget their fears in a happy life. It is particularly grateful for the help from the United States of America, through the Foster Parents' Scheme which in so many cases adopted children, where their English Foster Parents owing to war conditions here were unable wholly to maintain them without assistance. But the needs though reduced are still very great, as the following report will show, and only a steady stream of financial help can enable us to shoulder the responsibilities. We have never appealed in vain, and we are confident that the wonderful help the Committee has received in the past will be continued as long as the need remains. WORK FOR ADULT SPANIARDS. No less important was the work of the National Joint Committee for the adult Spanish refugees, who came to Britain after the end of the Civil War. Many from Madrid ; and later others were rescued from unspeakable conditions in French concentration camps. They were placed under the care of the British Committee for Refugees from Spain, a further Sub-Committee which has recently been amalgamated with the Central Committee. 470 adults in all passed through its hands. Each case needed special advice and help. Of these 142 have now passed out of its care altogether ; 84 as emigrants to South America, Mexico, China, Canada, Sweden and elsewhere. Eight as sailors on allied ships, 45 International Brigaders, and five have unfortunately died. An immense amount of work has been done, is being done, and must continue to be done, to give them advice and help on a wide variety of problems — emigration, medical attention, evacuation, police registration, air-raid injury and damage, suitable billets, and above all finding them employment, and instructing them in employment regulations — which become more complicated and difficult every day. The following is a short list of the type of work which is undertaken by the refugees. Many are now being placed in their own professions, and quite a number who were unskilled are steadily improving their lot. It is hoped in this way to help them prepare for the future, 292/946/38/24(IV)